2017
DOI: 10.1093/schbul/sbx004
|View full text |Cite
|
Sign up to set email alerts
|

Task-Related Functional Connectivity Analysis of Emotion Discrimination in a Family Study of Schizophrenia

Abstract: Poor emotion recognition is a core deficit in schizophrenia and is associated with poor functional outcome. Functional magnetic resonance imaging (fMRI) multivariate analysis methods were used to elucidate the neural underpinnings of face and emotion processing associated with both genetic liability and disease-specific effects. Schizophrenia patients, relatives, and controls completed a task that included 4 facial emotion discrimination conditions and an age discrimination condition during fMRI. Three functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 71 publications
1
23
0
Order By: Relevance
“…Through its broad pattern of connectivity with cortical and subcortical structures, the amygdala might play a broader role in the recognition of emotions, detecting and processing socially salient cues . These findings have also been corroborated by neuroimaging studies associating dysfunctions in negative and positive emotions processing in neuropsychiatric patients, with alterations in amygdala responses …”
Section: Emotion Recognition In Humansmentioning
confidence: 73%
See 1 more Smart Citation
“…Through its broad pattern of connectivity with cortical and subcortical structures, the amygdala might play a broader role in the recognition of emotions, detecting and processing socially salient cues . These findings have also been corroborated by neuroimaging studies associating dysfunctions in negative and positive emotions processing in neuropsychiatric patients, with alterations in amygdala responses …”
Section: Emotion Recognition In Humansmentioning
confidence: 73%
“…76 These findings have also been corroborated by neuroimaging studies associating dysfunctions in negative and positive emotions processing in neuropsychiatric patients, with alterations in amygdala responses. 17,[77][78][79] Additionally, a number of brain areas and connective pathways implicated in emotion perception and processing require further investigation. It is possible that within the same brain region there are circuit-or cell-specific heterogeneities that control different aspects of emotion recognition and processing.…”
Section: Emotion Recognition In Humansmentioning
confidence: 99%
“…Neuroimaging studies have implicated early top-down inhibition from anterior cingulate cortex to the amygdala in facial affect processing 9,10 . Increased amygdalar activation to stimuli with negative emotional salience has been found in schizophrenia 11,12 , along with reduced interaction between amygdala and frontoparietal cortex 13 . Nevertheless, it remains unclear how regional activations and network interactions result in behaviorally relevant emotion processing, and which components of this process contribute to dysfunctional facial affect processing in 22q11.2DS.…”
Section: Introductionmentioning
confidence: 96%
“…Here, we hypothesized that primary visual and motor processing would be preserved in individuals with 22q11.2DS, while frontolimbic interactions subserving bottom-up emotion-processing 6,7 would be disrupted in individuals with 22q11.2DS. We applied constrained principal component analysis (CPCA) 13,[20][21][22][23][24] to identify brain activation patterns evoked by images of faces, and quantified their time course of activation after emotion identification. Specifically, we used emotion identification task fMRI data 8,11,25 acquired from 58 individuals with 22q11.2DS identified through the 22q and You Center at the Children's Hospital of Philadelphia, examined as part of a prospective brain-behavior study of 22q11.2DS, and 58 age-, sex-, and race-matched healthy controls (HCs) from the Philadelphia Neurodevelopmental Cohort 26,27 .…”
Section: Introductionmentioning
confidence: 99%
“…Differences in amygdala activity and corticolimbic connectivity during emotion processing have also been found in patients with schizophrenia [42, 43]. Meta-analytic findings suggest hypoactivation of the amygdala in response to emotional facial expressions compared to healthy controls [44], whereas more recent studies reported hyperactivation in response to neutral facial expressions [45, 46].…”
Section: Introductionmentioning
confidence: 99%